The Banker’s oath and financial advice - Weitzel, Utz; Kirchler, Michael (Journal of Banking & Finance, 2023)
Financial misbehavior is widespread and costly. The Dutch government legally requires every employee in the financial sector to take a Hippocratic oath, the so-called “banker’s oath.” We investigate whether nudges that (in)directly remind financial advisers of their oath affect their service. In a large-scale audit study, professional auditors confronted 201 Dutch financial advisers with a conflict of interest. We find that when auditors apply a nudge that directly refers to the banker’s oath, advisers are less likely to prioritize bank’s interests. In additional prediction tasks, we find that Dutch regulators expect stronger effects of the oath than observed.